Predicting Satisfaction with Smart Irrigation Controllers and Their Long‐Term Use among Homeowners in Central Florida1. (5th July 2017) - Morera, Maria C.; Monaghan, Paul F.; Dukes, Michael D.; Breder, Eliza
Abstract: Studies throughout Florida have shown smart controllers can substantially reduce irrigation under residential high‐water use conditions. However, successful promotion requires understanding the link between controller performance and the mechanisms by which they are adopted. This article compares irrigation water‐use and survey data collected from households installed with soil moisture sensor and evapotranspiration controllers. The study investigated whether the relative change in irrigation use between two years preceding and two years following installation was a reliable predictor of a homeowner's satisfaction with the device and likelihood of continuing to use it. Results indicated relative changes in irrigation use were only significantly associated with the quality of controller programming. Satisfaction with the controller was largely attributable to satisfaction with the appearance of the landscape and the perceived water‐saving effectiveness of the controller whereas the likelihood of its continued use was only significantly predicted by the level of technical knowledge regarding its functioning and whether or not challenges were experienced with it. Targeting homeowners with supplemental user‐friendly information may best support their long‐term adoption of smart controllers while providing irrigation contractors with training in implementation techniques would represent an integrated strategy for added reductions in residential outdoor water use.